PENGARUH KINERJA KEUANGAN DAN VARIABEL MAKROEKONOMI TERHADAP HARGA SAHAM PERUSAHAAN AGRIKULTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Ismi Nurul Ilmi, - (2019)
This study aims to determine the effect of Financial Performance that is proxied by Current Ratio (CR), Return On Equity (ROE), and Debt to Equity Ratio (DER), and Macroeconomic Variables that are proxied by Inflation, Interest Rates, and Exchange Rates. The population in this study is an agricultural company listed on the Indonesia Stock Exchange (IDX) for the period 2013-2017. The sample selection technique used was purposive sampling and obtained 13 Agrukultur companies with a research period of five years to obtain 65 sample units in this study. Data analysis was performed using Microsoft Excel 2013 and hypothesis testing in this study used Panel Data Regression Analysis with the E-Views 9.0 program and a significance level of 5%. The results of the study partially show that, (1) liquidity (CR) doesn't have a significant effect on stock prices, (2) profitability (ROE) has a significant positive effect on stock prices, (3) debt policy (DER) has a significant positive effect on stock prices, ( 4) Inflation doesn't have significant effect on stock prices, (5) the interest rate doesn't have a significant effect on stock prices, and (6) the exchange rate doesn't have a significant effect on stock prices.